Pruning affects the vegetative balance of the wine grape (vitis vinifera l.) (2014)
The cultivation of grapes for the production of wine at altitudes between 2,200 and 2,600 masl started in the department of Boyacá in 1982. Quality wines are produced by the Ain Karim Vineyard in Ricaurte High. It is necessary to have wine grapes that possess suitable organoleptic compounds at harvest in order to guarantee quality grape must that can be converted into wine. For this, it is necessary to have a suitable ratio between the inflows and the outflows and to guarantee production, quality and vegetative sustainability over time, conserving the equilibrium and benefiting the productive potential of the vineyard. This study aimed to evaluate the productive and vegetative balance effect in the wine grape varieties (Vitis vinífera L.) Cabernet Sauvignon and Sauvignon Blanc in Sutamarchán-Boyacá, considering different pruning types (short, long, and mixed). A bifactorial, completely random statistical design was used. At the time of harvest, the fruit production and pruned wood were evaluated. The long-pruned vines presented the best behavior and the most balanced inflow/outflow ratio, while Sauvignon Blanc demonstrated a better productive yield. Meanwhile, the short and mixed prunings presented the better values for the ravaz index, indicating that they are more suitable for the conditions of the region, allowing for sustainability during the productive cycles of the wine grapes.